International aspects of organizational ethics in educational systems - Shapira-Lishchinsky, Orly (Studies in educational administration, 2018)
While previous research in educational administration has focused on how to combat students' tardiness, absenteeism, and disciplinary problems, only a few studies have focused on teachers' withdrawal behaviors, such as absenteeism and the intent to leave. This book takes a unique organizational approach towards understanding the concept of ethics in educational systems. It provides a global perspective and connects theory and praxis through team-based simulations, case studies and scenarios.It also allows researchers, educators and teachers, and educational leaders and administrators around the world to understand how they can develop an ethical culture in their schools. This understanding can encourage the development and assimilation of a code of ethics for teachers and educators and thecreation of a policy of intervention that can help to minimize teachers' withdrawal behaviors. In this way, the author presents an integrative approach towards creating a positive learning environment for teachers and students.